Epidemiology of latent tuberculosis infection in Japan-born and foreign-born children in Japan - Kasuya, Saori; Imai, Akiko; Uchimura, Kazuhiro; Ohkado, Akihiro; Kawatsu, Lisa (Western Pacific Surveillance and Response, 2023)
Objective: This study aims to compare the epidemiology of notifications of latent tuberculosis infection (LTBI) among Japan-born and foreign-born children in Japan between 2010 and 2020, and to assess the language used during LTBI case interviews with parents or caregivers of foreign-born children with LTBI during 2019.Methods: Our study consisted of two parts: (1) an analysis of national data from the Japan Tuberculosis Surveillance (JTBS) system on the epidemiology of LTBI among Japan-born and foreign-born children in Japan and (2) a survey of staff at public health centres that had registered at least one foreign-born child aged
Keywords: latent tuberculosis infection; emigrants and immigrants; children; Japan